Technology blueprint premier electronic / Iqbal Ali Mohd Azman - Mohd Azman, Iqbal Ali (2020)
This blueprint is on Premier Electronic which is a small business unit that provides services for the customer to get new electrical utility and appliances. Encik Iqbal Ali Mohd Azman is the sole owner and employee of Premier lectronic and this business is formed under sole proprietorship on 19th of May 2020. It is situated at Lot 33 Oakland Seremban 2, Jalan Haruan, Oakland Industrial Park, 70300 Seremban Negeri Sembilan which is a strategic location that has potential market in order to achieve the business’s market goals. Premier Electronic has identified three key factors that will be instrumental to its sustainability. The first factor is to ensure 100% customer satisfaction. This small business will make sure those repeat customer and customer referrals are valuable. Next, this business will also design, sell meaningful and valuable power protection products.